The complete mitochondrial genome of hybrid F2 from Acanthopagrus schlegelii (♀) × Pagrus major (♂). Issue 1 (2nd January 2019) - Chen, Shuyin; Zhang, Zhiyong; Zhu, Fei; Xu, Jin; Ji, Hongjiu; Wu, Guojun; Jia, Chaofeng; Meng, Qian
Abstract: The complete mitochondrial genome of hybrid F2 from Acanthopagrus schlegelii (♀) × Pagrus major (♂) was obtained using high-throughput sequencing technology. The circular genome was 16, 648 bp in length, consisting of 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and a control region. Overall, nucleotide composition was A: 28.02%, T: 27.88%, C: 27.93%, G: 16.17%. Nine genes were encoded on the light strand and the remaining 28 genes were encoded on the heavy strand. All protein initiation codons are ATG except for COI that begins with GTG. The phylogenetic analysis suggested that hybrid F2 of A. schlegelii (♀) × P. major (♂) was closest to A. schlegelii . The newly described mitochondrial genome may provide valuable data for the genetic and taxonomic research on artificial hybrid seabream.